Resistance of chimpanzee T cells to human immunodeficiency virus type 1 Tat-enhanced oxidative stress and apoptosis - Ehret, Andreas; Westendorp, Michael; Herr, Ingrid; Debatin, Klaus-Michael; Heeney, Jonathan L.; Frank, Rainer; Krammer, Peter H. (Journal of virology, 1996)
CD4+ T-cell depletion in AIDS patients involves induction of apoptosis in human immunodeficiency virus (HIV)-infected and noninfected T cells. The HIV type 1 (HIV-1)-transactivating protein Tat enhances apoptosis and activation-induced cell death (AICD) of human T cells. This effect is mediated by the CD95 (APO-1/Fas) receptor-CD95 ligand (CD95L) system and may be linked to the induction of oxidative stress by Tat. Here we show that HIV-1 Tat-induced oxidative stress is necessary for sensitized AICD in T cells caused by CD95L expression. Tat-enhanced apoptosis and CD95L expression in T cells are inhibited by neutralizing anti-Tat antibodies, antioxidants, and the Tat inhibitor Ro24-7429. Chimpanzees infected with HIV-1 show viral replication resembling early infection in humans but do not show T-cell depletion or progression towards AIDS. The cause for this discrepancy is unknown. Here we show that unlike Tat-treated T cells in humans, Tat-treated chimpanzee T cells do not show downregulation of manganese superoxide dismutase or signs of oxidative stress. Chimpanzee T cells are also resistant to Tat-enhanced apoptosis, AICD, and CD95L upregulation.
Gesehen am 21.10.2024